PRECISE KINEMATIC APPLICATIONS OF GPS: PROSPECTS AND CHALLENGES - Rizos, Chris; Han, Shaowei (Boletim de Ciências Geodésicas, 1998)
GPS kinematic positioning in the post-processed or in the real-time mode is now increasingly used for many surveying and navigation applications on land, at sea and in the air. Techniques range from the robust pseudo-range-based differential GPS (DGPS) techniques capable of delivering accuracies at the few metre level, to sophisticated carrier phase-based centimetre accuracy techniques. The distance from the mobile receiver to the nearest reference receiver may range from a few kilometres to hundreds of kilometres. As the receiver separation increases, the problems of accounting for distance-dependent biases grows. For carrier phasebased techniques reliable ambiguity resolution becomes an even greater challenge. In the case of DGPS, more appropriate implementations such as Wide Area DGPS become necessary. In this paper, the challenges, progress and outlook for high precision GPS kinematic positioning for the short-range, medium-range and long-range cases, in both the post-processing and real-time modes will be discussed. Although the focus will be on carrier phase-based systems, some comments will also be made with regards to DGPS systems. Several applications of kinematic GPS positioning will be considered, so as to demonstrate the engineering challenges in addition to GPS, that have to be addressed.